The impact of aggregate and sectoral fluctuations on training decisions - Vincenzo Caponi; Cevat Burc Kayahan; Miana Plesca (Institute for the Study of Labor (IZA), 2009)
So far the literature has found that the effect of macroeconomic fluctuations on training decisions is ambiguous. On the one hand, the opportunity cost to train is lower during downturns, and thus training should be counter-cyclical. On the other hand, a positive shock may be related to the adoption of new technologies and increased returns to skill, making training incidence pro-cyclical. Using the Canadian panel of Workplace and Employee Survey (WES) we find that (i) training moves counter-cyclical with the aggregate business cycle (more training during downturns), while at the same time (ii) the idiosyncratic sectoral shocks have a positive impact on training incidence (more training in sectors doing relatively better). This finding helps us understand training decisions by firms and has important theoretical and policy implications.
urn:nbn:de:101:1-20090323103
Keywords: E32; J24; 330; Training; business cycles; Betriebliche Bildungsarbeit; Bildungsverhalten; Konjunktur; Kanada